Derivation and evaluation of a multi-regime spray flamelet model - Olguín Astudillo, Hernán Andrés; Gutheil, Eva (Zeitschrift für physikalische Chemie, 2015)
Abstract The formulation of a comprehensive flamelet model to consider detailed - chemical reaction mechanisms in the simulation of turbulent spray - flames is a very challenging task due to the inherent multi-regime - structure of spray flames. Non-premixed, premixed, and - evaporation-controlled combustion regimes may be found in a single - spray flame. Recently, attempts have been made to extend classical - single regime flamelet models to more complex situations, where at - least two combustion regimes coexist. The objective of this work is to - develop a framework in which two-regime flamelet models can be - described and combined in order to advance the development of - a comprehensive flamelet model for turbulent spray flames. For this - purpose, a set of spray flamelet equations in terms of the mixture - fraction and a reaction progress variable is derived, which includes - the evaporation, characterizing the spray flames, and which describes - all combustion regimes appearing in spray flames. The two-regime and - single regime flamelet equations available in the literature are - retrieved from these multi-dimensional spray flamelet equations as - special cases. The derived set of spray flamelet equations is then - used to evaluate structures of laminar ethanol/air spray flames in the - counterflow configuration in order to determine the significance of - different combustion regimes. The present study concerns spray flames - with no pre-vaporized liquid in the oxidizing gas phase, and it is - found that only non-premixed and evaporation-controlled combustion - regimes exist, so that premixed effects may be neglected. Moreover, an - exact transport equation for the scalar dissipation rate is derived, - which explicitly takes spray evaporation and detailed transport into - account. This equation is then used to evaluate assumptions commonly - adopted in the literature. The results show that the spatial variation - of the mean molecular weight of the mixture may be neglected in the - formulation of the mixture fraction, but it may be significant for its - scalar dissipation rate. The assumption of unity Lewis number may lead - to non-physical values of the scalar dissipation rate of the mixture - fraction, whereas the use of a mass-averaged diffusion coefficient of - the mixture is a good approximation for the spray flames under - investigation.
Online veröffentlicht: 05.09.2014
Gesehen am 19.06.2020